Manufaktur Berkelanjutan Pada Sampah Elektronik: Kasus Sampah Kulkas - Agus Sutanto; Berry Yuliandra; Willy Pratama (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
The growth of the Wastes from Electric and Electronic Equipments (WEEEs) or e-waste is presently considered to be one of the rapid increasing wastes streams in the large city of Indonesia. Concurrently, the urban mining activities for e-waste by informal sectors have potential on the economic, social and environment dimension. The three dimensions form a triple bottom line that supports the principles of sustainability in the manufacturing. In this research, the observation in some remote areas in Padang is conducted to find out the model of e-waste collection system activities from the household and its economic potential, especially for refrigerators e-waste. The result shows that minimaly there are three models of the e-waste collecting system for refrigerator e-wastes. The model involves all the parties in urban mining activities such as e-waste collectorsfrom household, repair shops, collectors who continue the re-assembly and classify the e-waste and final collectors who did the cleaning, crushing, packing and transporting e-waste to another city to do the recycling process. In this e-waste collecting model the components of refrigerator e-waste could be reused, remanufactured and recycled. From the reassembly of therefrigerators it is obtained the material composition of 58.1% iron, 26.3% plastic,10.9% styrofoam 10.9%, 2.1% aluminum, 1.8% copper pipe, and 0.8% others. The highest cumulative retained value is obtained from this collecting system ranged between IDR 230.200 to 355.200, where some second-hand components may still be inreuse and remanufacture. This price is equivalent to 14.9% to 22.1% the purchase price of a new refrigerator.